Penguatan Literasi Keuangan Digital dan Pemasaran Online pada Usaha Tenun Batak Melayu - Lores, Linda; Setia Tarigan, Eka Dewi; Mas’ut, Mas’ut (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
One of the crucial factors in the success of a business is the ability to manage finances through a digital platform. This community service aims to improve digital financial literacy as well as online marketing skills of Rehani business actors. Activities include training in the use of digital platforms for marketing and transactions, assistance in digital financial management, and education on online transaction security. The implementation of activities includes initial studies, training and discussions, technical assistance, and the evaluation process. The results of the implementation of the community service show an increase in understanding and ability in employees and business actors in using digital financial applications, and show an increase in understanding in online marketing. This increase in literacy is expected to strengthen competitiveness and business development in the future.